Community-Based Circular Agribusiness: Market Validation, Pricing Logic, and Value-Chain Coordination for Village Livestock Waste Fertilizer in Rural Indonesia - Dhanang Eka Putra; Hariyono Rakhmad; Huda Ahmad Hudori; Raden Roro Lia Chairina; Mochamad Rizal Umami (FOUNDAE (Foundation of Advanced Education), 2025)
Village livestock waste presents both an environmental burden and an underutilized resource capable of strengthening rural livelihoods when transformed into marketable organic fertilizer. This study develops a community-based circular agribusiness model that integrates market validation, pricing analysis, and value-chain coordination to improve the commercial feasibility of waste-to-fertilizer initiatives in rural Indonesia. A convergent mixed-methods design was implemented, combining a Price Sensitivity Meter survey with Cost–Volume–Profit and Break-Even Point calculations, supported by a simplified Value Chain Analysis involving farmers, processors, kiosks, and local cooperative actors. Data were collected from 60 small-scale livestock households, 150 fertilizer users, and 12–15 key informants across Arjasa District. Findings indicate an acceptable price range of IDR 40,000–80,000 per 25-kg bag, with an optimal price point near IDR 60,000. At this level, contribution margins remain positive across direct, cooperative, and kiosk channels, with the break-even requirement estimated at 180–230 bags per month. The value-chain assessment reveals constraints related to moisture variability, inconsistent granulometry, and high last-mile distribution costs. Proposed coordination measures include minimum quality standards, scheduled collection and delivery routes, and simple offtake agreements with a 3–5% quality-based incentive. Together, these elements form a replicable empowerment-oriented model that enhances income stability, reduces waste, and supports community-driven resource governance. The study demonstrates that circular agribusiness, when anchored in market evidence and locally manageable coordination mechanisms, can contribute to socio-economic resilience and strengthen community participation in sustainable rural development